Asymmetry between the dominant and non-dominant legs in the lower limb biomechanics during single-leg landings in females - Wang, J.; Fu, W. (Advances in Mechanical Engineering, 2019)
This study aims to determine the effects of asymmetry on kinematics, kinetics, and changes in the center of pressure of the dominant and non-dominant legs during single-leg landings in female athletes. Fifteen healthy female collegiate soccer players performed dominant and non-dominant single-leg landings from a height of 40 cm. The three-dimensional kinematics and kinetics of the lower extremities were collected simultaneously with a 16-camera motion capture system and one force platform, respectively. Moreover, joint angle, joint range of motion, ground reaction force, joint moment, center-of-pressure, and absolute symmetry index (ASI%) were analyzed. Results corroborated that the range of motion in the knee and hip joints were significantly lower in the non-dominant than in the dominant leg. Meanwhile, the non-dominant leg exhibited higher medial-lateral center-of-pressure displacement than did the dominant leg. In addition, the ASI% for the peak ground reaction force and the loading rate exceeded 10% (peak ground reaction force: 11.31%, loading rate: 19.28%), which indicated asymmetry between the two legs during the single-leg landing impact. The findings also imply that for the female soccer players, the risk of injury (e.g. anterior cruciate ligament injury) can be higher in the non-dominant than in the dominant leg during unilateral dynamic movements.